The Role of Creative Economy-Based Startups on Member Economic Improvement and Economic Resilience - Beny Wibowo (Publindo Akademika, 2021)
This study aims to analyze the factors that make Gilak Brush start-up difficult to find members, evaluate the role of Gilak Brush start-up in dealing with human resource problems, and formulate solutions from Gilak Brush start-up to the economic resilience of members. This study used descriptive qualitative method. Data collection techniques through observation, interviews, literature study, internet, and documentation. The data analysis technique uses data reduction, categorization, data display and drawing conclusions. The results showed that the factors that made it difficult to get members consisted of prospective members' perceptions, standards, skills, work ethic, and idealism. The role to deal with resource problems is responded to by recruiting and selecting, developing and educating members, and organizing in accordance with limited human resources. The role of Gilak Brush start-up has an impact on economic resilience by increasing the economy per capita, there are two indicators to see this, namely the level of income and the fulfillment of living needs.